Fever of Unknown Origin: An Unusual Case - R. A. Bansal (Case Reports in Infectious Diseases, 2011)
Recurrent episodic fever of unknown origin (FUO) arising from tumour of the gastrointestinal tract is rare. We report an otherwise healthy 62-year-old man with recurrent circumscribed bouts of fever and raised CRP for 3 years who has remained well and fever-free 2 years after the removal of a well-differentiated adenocarcinoma of the colon. Occult colonic neoplasm should be considered and sought when routine investigations for FUO are negative.